A prosódia e a função comunicativa nas estereotipias da fala de indivíduos afásicos - Erica de Araujo Brandao Couto (2011)
This thesis describes for the first time in the Portuguese language, the verbal stereotypy of adult aphasic patients and analyzes the verbal expression in its prosodic aspects. In order to characterize the melodic components of these patients in their speech production, we compared aphasics and non aphasics subjects, aged between 20 to 50 years. The aim of this study is to investigate if the aphasic who uses the verbalstereotypy in his spontaneous speech makes proper use of the prosodic resources, to transmit information with communicative purposes. Pursuing the aim of this work, we adopted the Hallidays models (1970), although other works as Rizzo´s model (1981) were used to underlie our research. An experimental study with linguistic tasks as repetition and naming was delineated. In the repetition task the aphasic patients wereasked to repeat six illocutionary speech acts in the modalities of statement, request and command. It was expected that they reproduced the melodic variation of the statement, since the presence of a non-lexical verbal stereotype would not allow the reproduction of syllables, words and sentences. In the naming task the aphasic had to name elevenwords with a given number of syllables and a different accent. We considered that the naming task is representative of a more spontaneous speech and allows us to observe if the word produced by the aphasic resembles the word to be named, considering the number of syllables, reproduction of the accent and intonation. The collected data wererecorded, phonetically written and analyzed. Fundamental frequency, duration, rhythm and intensity were acoustically measured using acoustic analysis software PRAAT.The results in the repetition task pointed to a great variability in the duration of the statement, leading us to the conclusion that the knowledge of the physical size of the statement is not preserved. It was observed that in the non-lexical verbal stereotypy thefundamental frequency (F0) presents always a descendent curve in the statements independent of the modality, characterizing a peculiar and particular type of intonational pattern and the tessitura varies both between individuals and between statements of different types. Concerning rhythm, it was also observed a syllables type instead of an accentual or syllabic rhythm. Regarding intensity, the aphasics subjectspresented an ascendent-descendent curve, considered standard for normal speech. In the naming task the intonational pattern presented was an ascendent curve in the first syllables and descendant in the last one. The duration values were higher than the wordtarget and there is no correspondence between the word-target and the aphasicsemission referring the number of syllables, accent, etc. Our analysis show that the aphasic did not reproduce or use the prosodic patterns of intonation, duration and accent, leading us to consider that their speech is a product of automatic processing without cognitive control. Our study did not confirm the clinical observation that the aphasic presenting verbal stereotypy is able to transmit communicat ive information byvarying the intonation, intensity and rhythm of his speech. In this first attempt of describing the non-lexical verbal stereotypy, it was verified an intonation with very peculiar characteristics, indicating an individual component both in the segmental level as in the prosodic level. However, it is not possible to claim that the aphasic uses it intentionally to assist the communicative process.